2016
DOI: 10.3892/mmr.2016.4956
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of pomegranate on carbon tetrachloride hepatotoxicity in rats: A molecular and histopathological study

Abstract: The present study aimed to investigate the molecular mechanism underlying the hepatoprotective effects of pomegranate (POM) against oxidative stress in a rat model of carbon tetrachloride (CCl4)-induced liver damage. Injection of rats with CCl4 resulted in hepatic inflammation and lipid accumulation via the upregulation of interleukin (IL)‑6 and sterol regulatory element‑binding protein 1c (SREBP‑1c) mRNA expression. CCl4 induced downregulation of the anti‑inflammatory factors alpha 2‑macroglobulin (α‑2M) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This can find good support in the recent study of DEN/CCl4 Zhang et al [55] who reported that DEN via interaction with strategic macromolecules such as antioxidant enzymes, DNA, lipids, and DNA repairing system enzymes can induce HCC. Moreover, it is well accepted that CCl4 biotransformation by the help cytochrome P-450 usually converted to trichloromethyl free radical (CCl 3 *), and trichloromethyl proxy free radical (CCl 3 OO*) as two metabolites related to ROS generation, lipid peroxidation, and decrease of CAT, SOD, GST, and GPx enzymatic activities [[56], [57], [58]]. Moreover, the reported data are in concomitant with the previous study of Hussein & and Khalifa and Kadasa et al [59,60] who indicated significant reduction of antioxidant enzyme activities and their relative gene expression in DEN-induced rats comparing to control.…”
Section: Discussionmentioning
confidence: 99%
“…This can find good support in the recent study of DEN/CCl4 Zhang et al [55] who reported that DEN via interaction with strategic macromolecules such as antioxidant enzymes, DNA, lipids, and DNA repairing system enzymes can induce HCC. Moreover, it is well accepted that CCl4 biotransformation by the help cytochrome P-450 usually converted to trichloromethyl free radical (CCl 3 *), and trichloromethyl proxy free radical (CCl 3 OO*) as two metabolites related to ROS generation, lipid peroxidation, and decrease of CAT, SOD, GST, and GPx enzymatic activities [[56], [57], [58]]. Moreover, the reported data are in concomitant with the previous study of Hussein & and Khalifa and Kadasa et al [59,60] who indicated significant reduction of antioxidant enzyme activities and their relative gene expression in DEN-induced rats comparing to control.…”
Section: Discussionmentioning
confidence: 99%
“…After washing with PBS, sections were incubated with a goat anti-rabbit IgG biotin-conjugated secondary antibody (1:2,000; sc 2040; Santa Cruz Biotechnology, Inc., Dallas, TX). After incubation with horseradish peroxidase-labeled streptavidin, antibody binding was visualized using diaminobenzidine, and sections were counterstained with hematoxylin [22].…”
Section: Methodsmentioning
confidence: 99%
“…However, in our study down regulation of HSP70 expression level was achieved by each extracts (Pomo and Pistachio) by different percentages (Table 3, fig.9), but again pistachio extract in its nano form was the most powerful as an anti-inflammatory compared to pomegranate. This is may be interpreted upon the powerful flavonoids beside other phenolic compounds benzoic acid, and hydroxycinnamic acid derivatives, that have antioxidant properties exist in the nano pistachio to induce strong HSP70 immunoreactivity , prevent protein denaturation and succeeded to overcome TAA induced liver damage [91,92] .…”
Section: Discussionmentioning
confidence: 99%